1974
DOI: 10.1073/pnas.71.9.3465
|View full text |Cite
|
Sign up to set email alerts
|

A New Relaxed Mutant of Escherichia coli with an Altered 50S Ribosomal Subunit

Abstract: Cultures were grown with reciprocal shaking at 370 in either phosphate-buffered medium M9 (10) or in Tris medium (11) with 0.2% glucose (w/v) as energy source. These growth media contained 20 pg/ml of -proline, 20 pg/ml of zAeucine, 10 pg/ml of uracil, and 50 pg/ml of all other growth requirements. To achieve rapid amino-acid starvation, cultures were shifted by membrane filtration to growth medium lacking amino acids. For shift-down experiments, cultures were grown in medium containing 0.01% glucose and 0.2%o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 20 publications
2
59
1
1
Order By: Relevance
“…Furthermore, the full-length RelA proteins with mutations in the CTD (RelA-C612G, RelA-D637R, and RelA-C638F) were still found to be ribosome associated. Our findings are supported by the fact that in relC mutants, while the endogenous RelA remained ribosome bound, it maintained only 10% of its normal activity (9). Thus, it seems that even though in these cells the ribosomes contain a mutant form of ribosomal protein L11, they can still bind RelA.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the full-length RelA proteins with mutations in the CTD (RelA-C612G, RelA-D637R, and RelA-C638F) were still found to be ribosome associated. Our findings are supported by the fact that in relC mutants, while the endogenous RelA remained ribosome bound, it maintained only 10% of its normal activity (9). Thus, it seems that even though in these cells the ribosomes contain a mutant form of ribosomal protein L11, they can still bind RelA.…”
Section: Discussionsupporting
confidence: 75%
“…In vitro, ribosomes from the relC strain have only 10% of the (p)ppGpp synthetic activity of ribosomes from the wild-type strain (9). Previously in our laboratory, it was shown that when they were overexpressed separately in the relC strain, the synthetic activity of the full-length RelA was severely impaired, while the truncated N-terminal RelA fragment was active (29 sensitivity test.…”
Section: Resultsmentioning
confidence: 99%
“…Ochi seen on the gel, although it might have been hidden by another protein spot. Strain 63 can thus be classified as a relC mutant, and the missing protein was tentatively designated ST-L1 1 by analogy with E. coli and B. subtilis mutants which lack ribosomal proteins L11 and BS-L1 1, respectively (Friesen et al, 1974;Smith et al, 1978Smith et al, , 1980. Antibiotic resistance.…”
Section: Characterization Of the Re1 Mutantmentioning
confidence: 99%
“…Such mutations map in either the relA (1) or the relC (11,20) genes. The relC gene was later shown to be identical to rplK, the gene encoding ribosomal protein L11.…”
mentioning
confidence: 99%